1981
DOI: 10.1111/j.1365-2621.1981.tb04862.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and Evaluation of Pea Protein Isolate

Abstract: Laboratory and pile t plant processes were developed for producing pea protein isolate from field peas. Sodium proteinate and isoelectric products containing up to 90% protein were obtained by alkaline extraction and precipitation at the isoelectric point. Drying was carried out bj' freeze, spray and drum processes. Chemical analysis, functional properties, color and flavor of the dried isolates compared fav'jrably with their soy counterparts. Generally, the sodium protein,ktes exhibited more functionality tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
4
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 1 publication
9
43
4
1
Order By: Relevance
“…The protein content of all isolates prepared using isoelectric precipitation (IEP) ranged between 806 and 890 g/kg (wet weight basis, wb). Protein levels were similar to levels reported for other pea isolate products and ranged between 754 and 900 g/kg (1,(30)(31)(32). In this study, the lipid content varied considerably among isolates (5.1-55.0 g/kg) with higher lipid contents corresponding to lower protein levels in isolates.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The protein content of all isolates prepared using isoelectric precipitation (IEP) ranged between 806 and 890 g/kg (wet weight basis, wb). Protein levels were similar to levels reported for other pea isolate products and ranged between 754 and 900 g/kg (1,(30)(31)(32). In this study, the lipid content varied considerably among isolates (5.1-55.0 g/kg) with higher lipid contents corresponding to lower protein levels in isolates.…”
Section: Resultssupporting
confidence: 80%
“…Water hydration capacity values for all 7 cultivars were not significantly (p>0.05) different, ranging between 1.88 and 2.37 g/g (Table 4). Similar values for WHC were reported by Sumner et al (31), whereas Tomoskozi et al (40) reported WHC values of IEP pea protein to be lower (approximately 1.25 g/g). However, the WHC value for PPI has also been reported to be as high as approximately 4 g/g for both laboratory prepared isolates (1) and isolates prepared on a commercial scale (41).…”
Section: )supporting
confidence: 85%
See 1 more Smart Citation
“…However, opposite results were obtained concerning functional properties of soy and pea protein isolates. Some researches (Fernandez-Quintela et al 1997;Sun and Arntfield 2010) obtained better functionality of soy protein isolates, whereas others (Sumner et al 1981;Sosulski and McCurdy 1987;Aluko et al 2009) indicated to better properties for pea isolates. Variations in the results among different studies could be due to differences in the protein purity of the samples studied, method of protein isolation as well as the specific conditions used for the tests (Boye et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their relatively unfavorable protein quality (Gupta, 1983;Augustin and Klein, 1989;Friedman, 1996;Savage and Deo, 1989), they are regarded as an important source of protein in many developing countries. Extensive studies have been carried out to explore their functional properties and their uses as flours, protein isolates and concentrates (Sosulski et al, 1976;Sosulski and Youngs, 1979;Vose, 1980;Sumner et al, 1981;Sahasrabudhe et al, 1981).…”
Section: Utilization and Potentialmentioning
confidence: 99%